Air Pollution Modeling and its Application XX - Steyn, Douw G.; Rao, S. T.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Recent developments in air pollution modelling are explored as a series of contributions from researchers at the forefront of their field. This book on air pollution modelling and its application is focused on local, urban, regional and intercontinental modelling; data assimilation and air quality forecasting; model assessment and evaluation; aerosol transformation; the relationship between air quality and human health and the effects of climate change on air quality. It consists of a series of papers that were presented at the 30th NATO/SPS International Technical Meeting on Air Pollution Modelling and its Application held in San Francisco, U.S.A., May 18-22, 2009. It is intended as reference material for students and professors interested in air pollution modelling at the graduate level as well as researchers and professionals involved in developing and utilizing air pollution models.
Local and urban scale modeling -- Regional and intercontinental modelling -- Data assimilation and air quality -- Model assessment and verification -- Aerosols in the atmosphere -- Interactions between air quality and climate change -- Air quality and human health -- Special session of California 2000 field study.
Keywords: Environment; Pollution; Air pollution; Environment; Pollution, general; Atmospheric Protection/Air Quality Control/Air Pollution; Environmental Monitoring/Analysis.; Electronic books